IT IS RARE FOR MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) TO MAKE FINANCIAL REPORTS - Rusydi Abubakar; Nurul Hikmah Tanjung; Ainna Mahrum Nasution; Sri Wahyuni; Rico Nur Ilham (RADJA PUBLIKA, 2025)
This study aims to analyze the level of awareness and readiness of Micro, Small, and Medium Enterprises (MSMEs) in preparing financial and tax reports. The data used in this study is primary data. The data obtained were analyzed using qualitative and quantitative research methods. The results show that the level of awareness and readiness of MSMEs in preparing financial and tax reports is still relatively low. MSMEs with the support of regulators need to make extra efforts to minimize the obstacles faced when compiling financial and tax reports.